(3EYGfI GdWGdH GdfGhi aj TQM EQTGO GdZGhis - (3CHh YHO Gddg GdMSjf Hf CHi HcQ Hf EHQGgje Hf OGhO GdfRjdis; (3TQa GdOjf ESeGYjd Hf CHj HcQ Hf YHO Gddg Hf EHQGgje GdebQj GdTQLj GdMSjfj, GdTGhQj GdRHjOj Gdjefj,J (B837 (3g` s
(3ChdgG (B:s
(3GdMeO ddg efTF CUfGa GdaWQ CeG HYO aGYde Cf GdCTJZGd HGdYe ef CaVd GdWGYGJ hdeG cGf cJGH EQTGO GdZGhi ef CMSf eNJUQGJ Gdabg adeG fXQJg cPdc s
(3BNQgG (B:s
(3hgPG eG JjSQ ef EYGfI GdWGdH Ydi GdEQTGO Ydi MSH GdeQGO hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3Ydi ghGeTgG JUMjMGJ hJbjjOGJ ai ChdgG hBNQgG JedcGJ eMOKIs
(3cJHgG CMO JdGejP GdeDda ai MjGJg s
(3hGdEQTGO eNJUQ GdMGhi GdUZjQ dfLe GdOjf YHO GdZaGQ Hf YHO GdcQje GdbQhjfi GdTGaYi J(B/ 665(3g` s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
Keywords: (3Gdabg GdTGaYjs